Teachers as Change Agents in Private Schools in Azerbaijan - Vanatizada, Gunel (ADA University, 2025)
This thesis explores how private school teachers in Azerbaijan perceive themselves as change agents and examines how school administrations influence their capacity to be a change agent. A mixed-methods design was used to collect quantitative data from 85 teachers via surveys and qualitative insights through semi-structured interviews with five teachers and one school administrator from a private school in Baku. Research showed that most teachers felt supported and motivated to make change and saw themselves as innovators in their schools. However, they could not act due to challenges such as limited curriculum flexibility, lack of resources, heavy workload, and resistance from some colleagues who were afraid to adopt other methods. Parents who preferred exam-oriented instruction also questioned teachers, which meant going against a more holistic, skill-based learning approach. Almost half of the participants felt no consistent support from school administrators. These findings call for stronger administrative support to enable teachers to treat them as crucial change agents in sustainable educational change. Ultimately, the study suggests that teacher engagement is driven by more than personal initiative and depends on institutional conditions, including leadership style, recognition, and autonomy. The findings provide insights into teacher-led change in the private education sector in Azerbaijan and have practical implications for administrators and policymakers seeking to create more collaborative and dynamic learning environments. Future research with broader participation could further validate these outcomes and enhance generalizability
Keywords: Private school teachers -- Attitudes -- Azerbaijan.; Teachers as change agents -- Azerbaijan.; Educational change -- Administration -- Azerbaijan.; Teacher-administrator relationships -- Azerbaijan.; School management and organization -- Azerbaijan.; Education